A method for preparing a bi-interfaces electrocatalyst for preparing ethylene oxide and application thereof
By loading Ag onto a CeO2/SnO2 support, an Ag-CeO2/SnO2 catalyst was prepared, which solved the problems of poor selectivity and equipment corrosion of existing catalysts. This enabled the high-selectivity, low-energy-consumption epoxidation of ethylene to ethylene oxide and extended the catalyst life.
Patent Information
- Application Number
- CN202511224599.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-11-28
- Estimated Expiration
- 2045-08-29
AI Technical Summary
Existing catalysts for the epoxidation of ethylene to produce ethylene oxide suffer from poor selectivity, easy Ag migration affecting catalyst lifespan, and halogen dependence in the electrolysis system leading to equipment corrosion problems.
A dual-interface electrocatalyst preparation method was adopted, which involves loading Ag onto a CeO2/SnO2 support and then preparing the Ag-CeO2/SnO2 catalyst via electrochemical deposition in a halogen-free electrolysis system. The specific steps include support synthesis, silver loading, and electrocatalytic application. The molar ratio of tin and cerium and the electrolysis parameters were controlled to achieve in-situ generation of reactive oxygen species.
This method enables the production of ethylene oxide from ethylene with high selectivity and low energy consumption, avoiding equipment corrosion, extending catalyst lifespan, and improving catalyst stability and activity.
Smart Images

Figure CN120738681B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of electrocatalytic synthesis of ethylene oxide, and in particular to a preparation method of a double-interface electrocatalyst for preparing ethylene oxide and application thereof. BACKGROUND
[0002] Ethylene oxide (EO) is one of the important organic chemical products as a derivative of ethylene. In traditional industry, raw gas containing ethylene and oxygen components is subjected to catalytic oxidation to produce ethylene oxide, while generating byproducts such as carbon dioxide and water. The catalytic oxidation reaction is generally carried out at a high temperature of 200-270°C and a high pressure of 1-3 MPa, with an energy consumption of up to 19 MJ / kg EO. The selectivity and CO2 emission intensity are difficult to meet the requirements of economic benefits and carbon emission reduction of enterprises.
[0003] Patent CN202111187708.9 discloses an α-alumina carrier and a preparation method thereof, and a silver catalyst for ethylene epoxidation and an ethylene oxidation method. The α-A12O3 powder in a specific particle size range obtained by crushing the waste carrier with α-alumina as the main component is used as the raw material to prepare the carrier, realizing the reuse of resources. Patent CN202010797846.8 discloses a silver catalyst for ethylene epoxidation for preparing ethylene oxide and a preparation method thereof. The catalyst comprises an α-alumina carrier and silver, a rhenium additive, an alkali metal, and a M-salen complex deposited on the carrier, and is prepared by an impregnation method. The silver element content is 1-30 wt% of the total mass of the catalyst, the alkali metal element, rhenium element, and M-salen complex content are 5-2500 ppm, 10-2000 ppm, and 5-2000 ppm of the total mass of the catalyst, respectively, the metal M in the M-salen complex is Co, Mn, Ni, or Gu, and the epoxidation capacity of the catalyst is improved, showing good activity in the process of ethylene oxidation for producing ethylene oxide. Although the above-mentioned catalysts show good activity, the activity stability of the catalyst for catalyzing ethylene epoxidation to prepare ethylene oxide still needs to be further improved.
[0004] Compared with the traditional industrial preparation of ethylene oxide, the method of electrochemical catalytic ethylene epoxidation for preparing ethylene oxide is increasingly studied, which is due to the direct electron transfer mechanism of electrochemical reaction, avoiding the high energy consumption of high-temperature thermodynamic driving. In addition, in the traditional industrial preparation of ethylene oxide, oxygen directly participates in oxidation, leading to many side reactions, and the conversion rate of ethylene and the selectivity of EO are limited by thermodynamics. Oxygen directly participates in oxidation to generate carbon dioxide. The electrochemical method can be carried out at room temperature and pressure, and can directly use green electricity such as wind power and photovoltaic power to drive, which meets the goal of low-carbon production.
[0005] However, the existing electrochemical method has the bottleneck of relying on halogen (such as Br - / Cl - ) as oxidation mediators, leading to equipment corrosion, product contamination and catalyst deactivation. In addition, the low solubility of ethylene and energy consumption are also not up to the industrialization standard. Therefore, it is necessary to develop a halogen-free electrolysis system to avoid corrosion problems by designing a catalyst to generate active oxygen species in situ. SUMMARY
[0006] The purpose of the present application is to provide a preparation method of a double-interface electrocatalyst for preparing oxirane and its application, so as to solve the problems of poor selectivity, easy migration of Ag affecting the service life of the catalyst, and easy corrosion of the equipment in the existing halogen-dependent electrolysis system of the existing electrocatalyst for preparing oxirane from ethylene.
[0007] The purpose of the present application is achieved by the following technical solutions:
[0008] A preparation method of a double-interface electrocatalyst for preparing oxirane, the preparation method comprising the following steps:
[0009] (1) Synthesis of carrier: soluble tin salt and urea are dissolved in deionized water, stirred until completely transparent, then transferred to a high-pressure reaction kettle for high-temperature treatment, and after treatment, centrifuged to obtain white precipitate, which is washed, dried and calcined to obtain crystalline SnO2 nanoparticles;
[0010] The crystalline SnO2 nanoparticles are immersed in a soluble cerium salt solution, dried and calcined after immersion to obtain a CeO2 / SnO2 carrier;
[0011] (2) Silver is loaded on the CeO2 / SnO2 carrier to prepare an Ag-CeO2 / SnO2 catalyst.
[0012] Further, the soluble tin salt is tin chloride pentahydrate, and the molar ratio of tin chloride pentahydrate to urea is 1:3-1:5;
[0013] The soluble cerium salt is cerium nitrate hexahydrate, and the molar ratio of metal cerium and tin in the crystalline SnO2 nanoparticles to cerium nitrate hexahydrate is 1:4-10;
[0014] The mass of silver ions in the Ag-CeO2 / SnO2 catalyst accounts for 10-15% of the total mass of the catalyst.
[0015] Further, the method of loading silver on the CeO2 / SnO2 carrier is an electrochemical deposition method, and the specific method comprises the following steps:
[0016] The CeO2 / SnO2 carrier is mixed with an organic polymer and pressed into a sheet-shaped electrode, then placed in a mixed solution of AgNO3 and KNO3 for deposition, and after washing, drying and annealing, the Ag-CeO2 / SnO2 catalyst is prepared.
[0017] Further, the organic polymer is polytetrafluoroethylene, and the mass ratio of the CeO2 / SnO2 carrier to the polytetrafluoroethylene is 20:1.
[0018] The molar concentration ratio of AgNO3 to KNO3 in the mixed solution of AgNO3 and KNO3 is 1:1.5-4, and the pH of the mixed solution of AgNO3 and KNO3 is 3-4.
[0019] Further, the current density of the constant current in the deposition process is 2 mA / cm 2 , the time is 30 min, the pulse width is 10 ms, and the interval is 50 ms.
[0020] The annealing condition is 250℃ annealing for 1h under nitrogen protection.
[0021] Further, the method for loading silver onto the CeO2 / SnO2 carrier is an impregnation method, and the specific method comprises the following steps:
[0022] The CeO2 / SnO2 carrier is impregnated in an equal volume of silver nitrate solution, stirred, and then placed for 4-6h, and then dried and calcined to obtain an Ag-CeO2 / SnO2 catalyst.
[0023] Further, the concentration of the silver nitrate solution is 1-1.8mol / L, and the calcination condition is: in 5% H2 / Ar mixed gas, the heating rate is 5℃ / min, and the temperature is raised to 300℃ and continues to calcine for 2h.
[0024] A double-interface electrocatalyst for the epoxidation of ethylene to prepare ethylene oxide, prepared by the above method.
[0025] The application of the above double-interface electrocatalyst in the electrocatalytic epoxidation of ethylene to prepare ethylene oxide.
[0026] According to the application of the above double-interface electrocatalyst in the electrocatalytic epoxidation of ethylene to prepare ethylene oxide, the specific application process comprises the following steps:
[0027] S1: The electrolysis process is carried out in a double-tank electrolytic cell, the anode chamber of the electrolytic cell uses a titanium mesh coated with an Ag-CeO2 / SnO2 catalyst, the electrolyte is 0.5M H2SO4, the cathode chamber of the electrolytic cell is a Pt / C catalyst, the electrolyte is 1.0M KOH, and the anode chamber and the cathode chamber are separated by a diaphragm.
[0028] S2: ethylene is injected into the anode chamber, high-purity O2 is introduced into the cathode, the pH of the anode chamber is dynamically regulated to 2.5-3.0 by controlling the injection rate of H2SO4 and KOH in the electrolyte, the pH of the cathode chamber is 10.5-11.5, and the temperature is controlled at 25±2℃ to carry out electrochemical catalysis of ethylene and oxygen to prepare ethylene oxide.
[0029] Further, in the S2 step, the ethylene is pre-dissolved by a bubble generator before being injected into the anode chamber.
[0030] The present application has the following beneficial effects:
[0031] 1. The present application provides a preparation method of a double-interface electrocatalyst for preparing ethylene oxide and application thereof. The electrocatalyst realizes the green process of efficient electrochemical epoxidation of ethylene to prepare ethylene oxide (EO) in a halogen-free electrolysis system. Meanwhile, the present application breaks through the limitations of traditional high-temperature and high-pressure processes and existing electrochemical methods that depend on halogens by optimizing the catalyst heterojunction design and electrolysis parameters, so as to realize the industrial production goals of high selectivity, high Faraday efficiency and low energy consumption.
[0032] 2. The present application provides a preparation method of a double-interface electrocatalyst for preparing ethylene oxide and application thereof. The molar ratio of tin and cerium is regulated during the preparation of the carrier, so that the catalyst has good stability.
[0033] 3. The present application provides a preparation method of a double-interface electrocatalyst for preparing ethylene oxide and application thereof. The mass range of Ag loaded on the carrier is controlled, so that the catalyst not only shows high electrocatalytic activity, but also has high EO selectivity.
[0034] 4. The present application provides a preparation method of a double-interface electrocatalyst for preparing ethylene oxide and application thereof. Compared with the direct oxidation method, ethylene reacts with active oxygen species instead of directly reacting with oxygen, which can avoid excessive oxidation and improve the selectivity of ethylene oxide.
[0035] 5. The present application provides a preparation method of a double-interface electrocatalyst for preparing ethylene oxide and application thereof. Compared with the traditional halogen system, the electrolyte system can effectively prolong the service life of the equipment and avoid corrosion of the equipment caused by halogens. BRIEF DESCRIPTION OF DRAWINGS
[0036] Figure 1 The transmission electron microscope (TEM) spectrum of the catalyst prepared in Example 1 of the present application;
[0037] Figure 2 The transmission electron microscope (TEM) spectrum of the catalyst prepared in Example 2 of the present application;
[0038] Figure 3Figure 1 shows a schematic diagram of a two-compartment electrolytic cell for the electrocatalytic epoxidation of ethylene and oxygen to produce ethylene oxide for Example 5 of the present application.
[0039] Figure 4 Figure 4 shows a schematic diagram of the interfacial action of a bi- interface electrocatalyst for the present application.
[0040] Reference numerals:
[0041] 1. Power supply; 2. Cathode compartment; 3. Separator; 4. Anode compartment; 5. Anode compartment electrolyte; 6. Cathode compartment electrolyte; 7. Anode compartment electrode; 8. Cathode compartment electrode; 9. Two-compartment electrolytic cell. DETAILED DESCRIPTION
[0042] A number of exemplary embodiments of the present application are now described in detail below. The description herein of certain examples of the present application should not be taken to limit the scope of the present application, but rather, is intended to provide a more complete description of the various aspects, features, and embodiments of the present application.
[0043] It is to be understood that the terminology used herein is for the purpose of describing particular embodiments of the present application only and is not intended to limit the scope of the present application. In addition, where particular ranges of values are given, understand that each intervening value, to the upper or lower limit of the range is also specifically included. The upper and lower limits of these intervening values are also specifically included within the scope of the present application. These smaller ranges are not expressly delineated herein but are to be understood that each smaller range is included within the scope of the present application.
[0044] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. Although preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present application. All documents mentioned herein are incorporated by reference to disclose and describe the methods and / or materials in connection with which the documents are cited. In case of conflict between the present specification and any document incorporated by reference, the present specification will control.
[0045] Various modifications and changes can be made to the specific embodiments of the present application described herein without departing from the scope or spirit of the application. Other embodiments of the application will be apparent to those of ordinary skill in the art from the description and examples presented herein. The specification and examples given herein are exemplary and should not be used to limit the present application, unless otherwise specifically stated herein.
[0046] The reagents and equipment used in the present application are known products or obtained by purchasing commercially available products. The following is a description of the dual-interface electrocatalyst of the present application: In the Ag-CeO2 / SnO2 dual-interface catalyst, the dual-interface refers to the Ag-CeO2 interface and the Ag-SnO2 interface, and the heterojunction interface formed by the contact between Ag nanoparticles (NPs) and the CeO2 carrier. CeO2 has a high oxygen vacancy concentration and oxygen storage capacity (OSC), while Ag exists in a partially oxidized state (Ag + / Ag 0 ), forming a strong metal-support interaction (SMSI); SnO2 has a high affinity for oxygen, and its surface easily adsorbs OH generated by hydrolysis, while Ag provides C2H4 adsorption sites.
[0047] The preparation method of the catalyst of the present application is described in detail by the following examples.
[0048] Example 1:
[0049] (1) Carrier synthesis:
[0050] 175.3 g of SnCl4·5H2O and 90.09 g of urea were dissolved in 400 mL of deionized water to prepare a tin salt solution, which was stirred with a magnetic stirrer at a speed of 500 rpm for 30 min until the tin salt solution was completely transparent. The tin salt solution was then transferred to a high-pressure reaction kettle, which was sealed and heated to 180°C at a rate of 5°C / min, and then held at this temperature for 12 h. After the reaction was completed, the solution was naturally cooled to room temperature, and the white precipitate was collected by centrifugation at 8000 rpm for 10 min.
[0051] The white precipitate was washed with deionized water three times and then with anhydrous ethanol twice to remove Cl - residues (no turbidity was observed in the silver nitrate test, and the specific test method was as follows: silver nitrate standard solution was added dropwise to the precipitate washing liquid, and the liquid was shaken until no white flocculent material was observed, indicating that the chloride ions had been completely removed, i.e., no turbidity was observed in the silver nitrate test). After washing, the white precipitate was vacuum dried at 60°C for 12 h to obtain SnO2 precursor powder. The SnO2 precursor powder was then placed in a muffle furnace and heated to 400°C at a rate of 3°C / min, and then calcined for 2 h to obtain crystalline SnO2 nanoparticles with a BET specific surface area of 52 m 2 / g and a particle size of 105±15 nm as characterized by transmission electron microscopy.
[0052] Ce(NO3)3.6H2O was dissolved in 45 mL of deionized water and ultrasonically dispersed for 10 min to prepare a cerium salt solution. 50 g of crystalline Sn02 nanoparticles were immersed in the cerium salt solution, stirred for 30 min, and then left to stand for 6 h. After the immersion was completed, the precursor powder was obtained by rotary evaporation at 80°C until dry. The precursor powder was placed in a muffle furnace and calcined at 350°C for 3 h in an air atmosphere at a heating rate of 2°C / min to decompose the cerium nitrate into Ce02. Then, the precursor powder was placed in a tube furnace and treated at 500°C for 2 h in a 5% H2 / Ar mixed gas at a heating rate of 5°C / min to form an oxygen vacancy Sn02 / Ce02 support. The oxygen vacancy here refers to a defect left after oxygen is separated from the lattice, which is a kind of point defect. The concentration of the oxygen vacancy was 1.7 x 1018cm-3, which was detected by electron paramagnetic resonance (EPR). 20 cm -3 .
[0053] (2) Preparation of 10% Ag-Ce02 / Sn02 catalyst by impregnation method
[0054] Silver nitrate solution was prepared by dissolving 2.78 g of AgN03 in 20 mL of deionized water and ultrasonically dispersing for 10 min. 10 g of Sn02 / Ce02 support was immersed in the silver nitrate solution, magnetically stirred for 1 h, and then left to stand for 5 h. After that, the precursor powder was obtained by rotary evaporation at 80°C until dry, vacuum drying at 60°C for 12 h, and then reduction at 300°C for 2 h in a 5% H2 / Ar mixed gas at a heating rate of 5°C / min to obtain an Ag-Ce02 / Sn02 catalyst. The size of the Ag NPs in the prepared catalyst was 20-120 nm (characterized by transmission electron microscopy (TEM), and the specific spectrum is shown in Figure 1 Fig. 1), and the actual loading mass of silver ions was about 10% of the total mass of the catalyst (including loss).
[0055] Example 2:
[0056] (1) Support synthesis:
[0057] A tin salt solution was prepared by dissolving 175.3 g of SnCl4.5H2O and 90.09 g of urea in 400 mL of deionized water. The tin salt solution was stirred with a magnetic stirrer at a speed of 500 rpm for 30 min until it became completely transparent. The tin salt solution was then transferred to a high-pressure reaction kettle, sealed, and heated at a rate of 5°C / min to 180°C. The solution was kept at a constant temperature for 12 h. After the reaction was completed, the solution was naturally cooled to room temperature. The white precipitate was collected by centrifugation at 8000 rpm for 10 min.
[0058] The white precipitate was washed with deionized water three times and then with anhydrous ethanol twice to remove Cl -Residual (no turbidity detected by silver nitrate test). After washing, the white precipitate was vacuum dried at 60°C for 12 h to obtain SnO2 precursor powder. The SnO2 precursor powder was then calcined in a muffle furnace at a heating rate of 3°C / min to 400°C for 2 h to obtain crystalline SnO2 nanoparticles (BET specific surface area ~ 52 m 2 / g, TEM characterization particle size 105 ± 15 nm).
[0059] Ce(NO3)3.6H2O was dissolved in 25 mL of deionized water and ultrasonically dispersed for 10 min to prepare a cerium salt solution. 50 g of crystalline SnO2 nanoparticles were immersed in the cerium salt solution, stirred for 30 min, and then left to stand for 6 h. After the immersion was completed, the precursor powder was obtained by rotary evaporation at 80°C until dry. The precursor powder was placed in a muffle furnace and calcined at 350°C for 3 h in an air atmosphere at a heating rate of 2°C / min to decompose the cerium nitrate into CeO2. Then, the calcined powder was placed in a tube furnace and treated at 500°C for 2 h in a 5% H2 / Ar mixed gas atmosphere at a heating rate of 5°C / min to form an oxygen vacancy CeO2 / SnO2 support (EPR electron paramagnetic resonance detection concentration 1.7 x 10 20 cm -3 ).
[0060] (2) Preparation of 12% Ag-CeO2 / SnO2 catalyst by electrochemical deposition method
[0061] 10 g of SnO2 / CeO2 support was mixed with 0.5 g of polytetrafluoroethylene (PTFE). After mixing the materials, the mixture was bidirectionally pressed by a hydraulic pellet press, and the pressure was maintained for 90 min. The voids were eliminated by releasing the pressure four times, and a sheet-shaped electrode (area 5 cm 2 , thickness 1 mm) was prepared.
[0062] The electrolyte in the electrochemical deposition tank was a mixed solution of 0.1 M AgNO3 and 0.2 M KNO3, and the pH of the electrolyte was adjusted to 4 by nitric acid. The constant current deposition parameters were a current density of 2 mA / cm² and a time of 30 min, and the deposition amount was controlled to be 12% Ag. The pulse width was 10 ms, and the interval was 50 ms to inhibit dendrite growth. The electrode was washed with deionized water and vacuum dried at 60°C for 6 h. The 12% Ag-CeO2 / SnO2 catalyst was obtained by annealing at 250°C for 1 h under nitrogen protection. The size of the Ag NPs in the prepared catalyst was 30-80 nm, as shown in the specific transmission electron microscopy (TEM) spectrum Figure 2 , and the mass of silver ions accounted for 12% of the total mass of the catalyst.
[0063] Example 3
[0064] The support preparation method was the same as in Example 2, and the electrochemical deposition method was as follows:
[0065] 10 g of Sn02 / Ce02 support was mixed with 0.5 g of polytetrafluoroethylene (PTFE), and after mixing the material, it was pressed in two directions by a hydraulic press, with a holding pressure of 90 minutes, and four times of air release to eliminate voids, to form a sheet-shaped electrode (area 5 cm 2 , thickness 1 mm).
[0066] The electrolyte in the electrochemical deposition tank was a mixed solution of 0.1 M AgN03 and 0.15 M KNO3, and the pH of the electrolyte was adjusted by nitric acid to be 3. The constant current deposition parameters were current density 2 mA / cm 2 , time 30 min, deposition amount control 15% Ag, pulse width 10 ms, interval 50 ms, and inhibition of dendrite growth. Deionized water was used for rinsing, and vacuum drying was performed at 60 °C for 6 h. Annealing was performed at 250 °C for 1 h under nitrogen protection, to obtain a 15% Ag-Ce02 / Sn02 catalyst. The size of the Ag NPs in the prepared catalyst was 30-80 nm, and the mass of silver ions accounted for 15% of the total mass.
[0067] Example 4
[0068] The support preparation method was the same as that in Example 2, and the electrochemical deposition method was as follows:
[0069] 20 g of Sn02 / Ce02 support was mixed with 1 g of polytetrafluoroethylene (PTFE), and after mixing the material, it was pressed in two directions by a hydraulic press, with a holding pressure of 90 minutes, and four times of air release to eliminate voids, to form a sheet-shaped electrode (area 10 cm 2 , thickness 1 mm).
[0070] The electrolyte in the electrochemical deposition tank was a mixed solution of 0.5 M AgN03 and 2 M KNO3, and the pH of the electrolyte was adjusted by nitric acid to be 3. The constant current deposition parameters were current density 2 mA / cm², time 30 min, deposition amount control 10% Ag, pulse width 10 ms, interval 50 ms, and inhibition of dendrite growth. Deionized water was used for rinsing, and vacuum drying was performed at 60 °C for 6 h. Annealing was performed at 250 °C for 1 h under nitrogen protection, to obtain a 10% Ag-Ce02 / Sn02 catalyst. The size of the Ag NPs in the prepared catalyst was 30-80 nm, and the mass of silver ions accounted for 10% of the total mass.
[0071] Comparative Example 1
[0072] In the support preparation process, the molar ratio of crystalline Sn02 nanoparticles to tin and cerium in cerium nitrate hexahydrate was 1:1, and the other conditions were the same as in Example 1.
[0073] Comparative Example 2
[0074] In the catalyst preparation process, the Ag deposition amount was controlled to be 20%, and the other conditions were the same as in Example 2.
[0075] Example 5
[0076] The method for preparing ethylene oxide by electrocatalytic ethylene epoxidation specifically comprises the following steps.
[0077] S1: The electrolysis process is carried out in a double-tank electrolytic cell 9, and a specific double-tank electrolytic cell 9 device schematic diagram is shown in Figure 3 , the anode chamber electrode 7 of the anode chamber 4 adopts a titanium mesh coated with the Ag-CeO2 / SnO2 catalyst (10 mg / cm 2 ) prepared in Examples 1-4 and Comparative Examples 1-2, and the anode electrolyte 5 adopts 0.5 M H2SO4, replacing Br - / Cl - active ions in the traditional halogen electrolyte. The high oxygen affinity of tin oxide on the electrode can preferentially adsorb water molecules, so that the intermediate product oxygen intermediate or hydroxyl intermediate stays on the electrode surface for a longer time, which can delay the generation of O2, avoid the direct oxidation of ethylene and oxygen to generate carbon dioxide, and reduce the selectivity of ethylene oxide. The cathode chamber electrode 8 of the cathode chamber 2 of the electrolytic cell is a titanium mesh coated with a Pt / C catalyst, and the specific components are mixed according to the following weight parts: 15-20 parts by weight of platinum carbon catalyst, 35-40 parts by weight of deionized water, 35-40 parts by weight of isopropyl alcohol, and 5-10 parts by weight of polystyrene sulfonate as an ionomer. After the above components are mixed, a slurry is prepared, the solid content is controlled to be 0.5-1.5, and the slurry is bidirectionally pressed by a hydraulic blanking machine for 90 minutes, and the voids are eliminated by releasing gas four times to press into a sheet-shaped electrode (area 5 cm 2 , thickness 1 mm). Then, the slurry is bidirectionally pressed by a hydraulic blanking machine for 90 minutes, and the voids are eliminated by releasing gas three times to press into a sheet-shaped electrode (area 5 cm 2 , thickness 1 mm), and the cathode chamber electrolyte 6 is 1.0 M KOH. The anode chamber 4 and the cathode chamber 2 are separated by a diaphragm 3, and the diaphragm 3 uses Nafion117 (fluorine-containing sulfonic acid type ion exchange membrane developed by DuPont). The platinum carbon catalyst is a commercially available product, which is purchased from Ningbo Zhongke Kexin New Energy Technology Co., Ltd.
[0078] Method for coating catalyst on titanium mesh: After the surface of the titanium mesh is pickled to remove the surface oxide layer and increase the roughness, the adhesion of the catalyst is enhanced. The catalyst powder and the polyacrylic acid binder are mixed and stirred in a mass ratio of 1:10, combined with ultrasonic oscillation to remove bubbles, and then coated by spraying. After coating, vacuum drying is performed, and the coating thickness is 100-200 microns.
[0079] S2: Ethylene purified by molecular sieve (purity > 99.9%) was bubbled into the anode chamber 4 of the electrolytic cell after pre-dissolution (solubility increased to 0.12 mol / L) by a peristaltic pump. High-purity O2 was introduced into the cathode chamber 2 (flow rate 50 mL / min).
[0080] The pH was displayed by a sensor, and the pH of the anode chamber 4 was dynamically controlled to 2.5-3.0 (deviation ± 0.1), and the pH of the cathode chamber 2 was controlled to 10.5-11.5 by controlling the injection rate of H2SO4 and KOH to change the pH. The temperature in the double-cell electrolytic cell 9 was controlled at 25±2℃, and the thermal stability was maintained by a jacketed water cooling system.
[0081] Example 6
[0082] In the S2 step, the pH of the anode chamber 4 was dynamically controlled to 4.0 by controlling the injection rate of the electrolyte H2SO4 and KOH, and the pH of the cathode chamber 2 was controlled to 8.5, and the others were the same as in Example 5.
[0083] The reaction time was 8h, and the activity and selectivity were detected by gas chromatography (Agilent 7890B).
[0084] The final detection results of the electrocatalytic activity and selectivity of the specifically prepared catalyst using the electrocatalytic method of Example 5 are shown in Table 1 below.
[0085] Table 1
[0086]
[0087] From the activity and selectivity data in Table 1 above, it can be seen that in Comparative Example 2, increasing the content of Ag in the catalyst did not increase its activity, but rather decreased it. This is mainly due to the increase in Ag loading, which causes the silver crystal grains in the catalyst to agglomerate, which is not conducive to the catalytic performance of the catalyst.
[0088] In the electrocatalytic reaction of ethylene epoxidation, the core function of the Ag-CeO2 interface is to activate ethylene (*C2H4, i.e. ethylene intermediate) and optimize adsorption, and the core function of the Ag-SnO2 interface is to promote water dissociation to generate *OH (hydroxyl intermediate) and inhibit side reactions. The specific electrocatalytic reaction process and catalyst double-interface interaction diagram are as follows: Figure 4The synergistic advantages of Ag-CeO2 and Ag-SnO2 in Ag-CeO2 / SnO2 catalyst are that Ag-CeO2 interface provides activated C2H4, Ag-SnO2 interface provides hydroxyl intermediates, both of which are spatially coupled by Ag NPs to avoid diffusion limitations of intermediates, and the oxygen vacancies of CeO2 and the oxygen affinity of SnO2 are complementary to balance the oxidation (C2H4 activation to generate ethylene intermediates) and reduction (hydroxyl intermediates) rates and inhibit excessive oxidation byproducts (such as CO2). This synergistic effect can be seen from the fact that changing the molar ratio of tin and cerium in the above Comparative Example 1 affects the selectivity of the catalyst.
[0089] The final detection results of the electrocatalytic activity and selectivity of the catalysts prepared in Examples 1-4 are shown in Table 2 below using the electrocatalytic method of Example 6.
[0090] Table 2
[0091]
[0092] As can be seen from the results of the activity and selectivity of the catalysts detected under the electrocatalytic reaction conditions of Example 5 and Example 6, i.e., in combination with the detection data of Table 1 and Table 2, when the regulated pH is 4, the activity of the catalyst has a significant decreasing trend, and the selectivity is not greatly affected.
[0093] In order to detect the stability of the catalyst, the activity attenuation of the catalyst was detected after continuous operation for 120 h under the electrocatalytic reaction conditions of Example 5. The activity attenuation was expressed as the ratio (in percentage) of the difference between the activity of the catalyst at 120 h and the activity at 1 h of reaction to the activity at 1 h of reaction. The specific summary is shown in Table 3 below.
[0094] Table 3
[0095]
[0096] As can be seen from Table 3 above, the activity attenuation rate of the catalyst prepared in Comparative Example 1 is greater than 15%, and the catalyst performance is unstable. Ag is combined on the carrier by electrochemical bond, which is better than physical adsorption. The catalyst prepared in Comparative Example 1 has poor stability, and Ag is easy to migrate.
[0097] The XPS of the catalyst prepared in Example 2 after running for 120 hours was detected, and the XPS showed that Ag was not dissolved, indicating that the Ag of the catalyst prepared in Example 2 was firmly loaded. In order to verify that when the catalyst is prepared by the electrochemical deposition method, the molar ratio of the crystalline SnO2 nanoparticles in the carrier to the tin and cerium in the cerium nitrate hexahydrate is 1:1, and the preparation method is the same as that of Example 2, then the activity attenuation of the catalyst prepared by the method is detected after the catalyst is continuously run for 120 hours under the electro-catalytic reaction conditions of Example 5, and it is found that the final detection activity attenuation rate is 12%, which is lower than 18% of Comparative Example 1, and thus it can be seen that compared with the method of loading active Ag by the impregnation method, changing the molar ratio of the tin and cerium in the carrier has a greater impact on the stability of the catalyst prepared by the electrochemical deposition method.
[0098] XPS is X-ray photoelectron spectroscopy, which is used for detecting element composition and quantitative analysis, and is used for analyzing chemical valence change and characterizing surface and interface characteristics, and is used for analyzing element composition in the present application.
[0099] The above is only a preferred embodiment of the present application, and of course cannot limit the scope of protection of the present application, and it should be pointed out that for ordinary skilled in the art, without departing from the principles of the present application, a number of improvements and changes can be made, and these improvements and changes are also considered to be within the scope of protection of the present application.
Claims
1. A method for the preparation of a bi- interfaced electrocatalyst for the production of ethylene oxide, characterized in that, The preparation method comprises the following steps: (1) carrier synthesis: a soluble tin salt and urea are dissolved in deionized water, stirred until completely transparent, then transferred to a high-pressure reaction kettle for high-temperature treatment, and after treatment, centrifuged to obtain a white precipitate, which is washed, dried and calcined to obtain crystalline SnO2 nanoparticles; The crystalline SnO2 nanoparticles are immersed in a soluble cerium salt solution, dried and calcined after immersion to obtain a CeO2 / SnO2 carrier; (2) silver is loaded on the CeO2 / SnO2 carrier to prepare an Ag-CeO2 / SnO2 catalyst.
2. The method of claim 1, wherein the method is characterized by, The soluble tin salt is tin chloride pentahydrate, and the molar ratio of tin chloride pentahydrate to urea is 1:3-5; The soluble cerium salt is cerium nitrate hexahydrate, and the molar ratio of metal cerium in cerium nitrate hexahydrate to tin in the crystalline SnO2 nanoparticles is 1:4-10; The mass of silver ions in the Ag-CeO2 / SnO2 catalyst accounts for 10-15% of the total mass of the catalyst.
3. The method of claim 1, wherein the method is characterized by, The method for loading silver on the CeO2 / SnO2 carrier is an electrochemical deposition method, and the specific method comprises the following steps: The CeO2 / SnO2 carrier is mixed with an organic polymer, then pressed into a sheet-shaped electrode, and then placed in a mixed solution of AgNO3 and KNO3 for deposition, and then washed, dried and annealed to obtain an Ag-CeO2 / SnO2 catalyst.
4. The method of claim 3, wherein the method further comprises: The organic polymer is polytetrafluoroethylene, and the mass ratio of the CeO2 / SnO2 carrier to polytetrafluoroethylene is 20:1; The concentration ratio of AgNO3 to KNO3 in the mixed solution of AgNO3 and KNO3 is 1:1.5-4, and the pH of the mixed solution of AgNO3 and KNO3 is 3-4.
5. The method of claim 3, wherein the method further comprises: The current density of the constant current in the deposition process is 2 mA / cm², the time is 30 min, the pulse width is 10 ms, and the interval is 50 ms; The annealing condition is 250°C for 1 h under nitrogen protection.
6. The method of claim 1, wherein the bi-interfacial electrocatalyst is prepared by the steps of: The method for loading silver on the CeO2 / SnO2 carrier is an immersion method, and the specific method comprises the following steps: The CeO2 / SnO2 carrier is immersed in an equal volume of silver nitrate solution, stirred and then left to stand for 4-6 h, and then dried and calcined to obtain an Ag-CeO2 / SnO2 catalyst; The concentration of the silver nitrate solution is 1-1.8 mol / L, and the calcination condition is: in a 5% H2 / Ar mixed gas, the heating rate is 5°C / min, the temperature is raised to 300°C, and the calcination continues for 2 h.
7. A double-interface electrocatalyst prepared by the preparation method of any one of the double-interface electrocatalysts in claims 1-6.
8. The use of the double-interface electrocatalyst in claim 7 for electrocatalytic ethylene epoxidation to prepare ethylene oxide.
9. Use of a bi-interfacial electrocatalyst according to claim 8 for the electrocatalytic ethylene epoxidation to produce ethylene oxide, characterized in that, The specific application process comprises the following steps: S1: The electrolysis process is carried out in a dual-cell electrolytic cell (9). The anode chamber (4) of the dual-cell electrolytic cell (9) uses a titanium mesh coated with Ag-CeO2 / SnO2 catalyst. The electrolyte (5) in the anode chamber is 0.5 M H2SO4. The cathode chamber (2) of the dual-cell electrolytic cell (9) is Pt / C catalyst. The cathode electrolyte (6) is 1.0 M KOH. The anode chamber (4) and the cathode chamber (2) are separated by a diaphragm (3). S2: Ethylene is injected into the anode chamber (4), and high-purity O2 is introduced into the cathode chamber (2). The pH of the anode chamber (4) is dynamically adjusted to 2.5~3.0 and the pH of the cathode chamber (2) is adjusted to 10.5~11.5 by controlling the injection rate of the electrolyte H2SO4 and KOH. The temperature is controlled at 25±2℃ to electrochemically catalyze the production of ethylene oxide from ethylene and oxygen.
10. Use of a bi-interfacial electrocatalyst according to claim 9 for the electrocatalytic ethylene epoxidation to produce ethylene oxide, characterized in that, In step S2, ethylene is pre-dissolved by a bubbler before being injected into the anode chamber (4).
Citation Information
Patent Citations
A silver catalyst for preparing ethylene oxide by epoxidation of ethylene and preparation method thereof
CN114054090B
Alpha-alumina carrier and preparation method thereof, silver catalyst for ethylene epoxidation and ethylene oxidation method
CN115957732B
Method for preparing ethylene oxide through electrocatalytic oxidation of ethylene
CN104805465A
CeO2-SnO2 compound oxide catalyst and production method and application thereof
CN110756185A